Holothuria leucospilota Population in Satang Besar Island, Sarawak, Malaysia - Harith, Mohd Nasarudin; Md Desa, Muhammad Hasanol Isyraf; Ilias, Zaidnuddin (International Journal of Zoology, 2018)
Holothuria leucospilota or locally known as “Patola” is currently considered the most abundant sea cucumber species in Malaysia. This coral reef-dwelling species is not in danger of extinction in comparison to commercial sea cucumbers such as “gamat.” However, overfishing activities in addition to lack of fishing regulations in Malaysia could put this species at risk of extinction in the future. It is important to conduct research on the sea cucumber community in Sarawak because the data can be used as reliable information for future research. Therefore, this study is carried out to quantify and estimate the Holothuria leucospilota population from an intertidal area of Satang Besar Island, Sarawak, Malaysia. Ten stations surrounding the island were selected as the location for this study. A total number of 203 individuals of Holothuria leucospilota were recorded and estimation of the population that inhabits the island’s intertidal area was 609 individuals. RELATE test showed relationships between species population and water parameters, namely, temperature, salinity, and pH. Results from this study are important as a baseline data that might contribute to the sustainable management of Sarawak, Malaysia’s sea cucumber in the future. Future work suggestions include addition of subtidal samples and other factors, namely, seawater nutrients and feeding environment, that should be done to better understand the population.